2007
DOI: 10.2214/ajr.05.1174
|View full text |Cite
|
Sign up to set email alerts
|

CT Features of Pancreatic Fistula After Pancreaticoduodenectomy

Abstract: A fluid collection seen on CT around the pancreaticojejunostomy site and in the pancreatic bed may be caused by pancreatic fistula in patients who have undergone pancreaticoduodenectomy. CT depiction of air bubbles in the fluid at these sites may strongly suggest the diagnosis of pancreatic fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 16 publications
0
22
0
3
Order By: Relevance
“…Reoperation was necessary in case of sepsis sustained by complex collections not sufficiently drained by percutaneous procedures, in case of complete dehiscence of the anastomosis, with evidence of air bubbles near the anastomosis at the CT scan [8,9,11] and/or septic status and in case of late bleeding provoked by the fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Reoperation was necessary in case of sepsis sustained by complex collections not sufficiently drained by percutaneous procedures, in case of complete dehiscence of the anastomosis, with evidence of air bubbles near the anastomosis at the CT scan [8,9,11] and/or septic status and in case of late bleeding provoked by the fistula.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of air bubbles was recorded for each fluid collection. The radiologists considered any fluid collection adjacent to the pancreaticogastric or pancreaticojejunal anastomosis a pancreatic fistula [26].…”
Section: Image Analysismentioning
confidence: 99%
“…The interval between surgery and CT was based on observations that the diagnosis of pancreatic fistula is made an average of 7 days after pancreaticoduodenectomy [5,14,15]. One study [26] showed that a fluid collection seen around the pancreaticojejunostomy site and in the pancreatic bed on CT images may be caused by pancreatic fistula in patients who have undergone pancreaticoduodenectomy. That study, however, was limited by selection bias: Only patients with clinically suspected complications were included.…”
Section: Ct Of Pancreatic Fistulamentioning
confidence: 99%
“…According to widespread opinions in the literature, postoperative complications after pancreatic surgery including POPF, can be identified by cross-sectional imaging [789]. It is also generally accepted that US is not a reliable imaging modality for deep abdominal organs and pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Although routine imaging is generally not used for the early identification of POPF [67], with the advances in the technology of US, it is not surprising that surgeons tend to perform an transabdominal US to evaluate the potential abdominal fluid collections. There have been very limited data published on transaabdominal US examination during the early postoperative period after pancreatic surgery.…”
Section: Introductionmentioning
confidence: 99%